THE USE OF OBSERVATIONAL TECHNIQUES IN EVALUATING LEARNING OUTCOMES IN SCIENCE AND VOCATIONAL EDUCATION - A., Faremi Y. (Sokoto Educational Review, 2020)
Evaluation is the end product of Test, measurement, and Assessment. Learning outcomes in skill areas and behaviour changes in personal social development are especially difficult to evaluation with the usual paper and pencil test. The aim of this paper is to examine the various methods to be adopted by a classroom teacher in evaluating learning outcome and development of science and vocational Education. The paper further discusses the use of observation techniques (Anecdotal Records, rating scale, and Checklist) as the instrument for measuring non-cognitive domain of any learning outcomes. The paper also recommend that science and vocational teachers, school administrator, Curriculum planners, and different examination bodies should inculcate the spirit of using the checklist, rating scale and Anecdotal techniques in evaluating learning and development of science and vocational Education.